2008
DOI: 10.1590/s1519-69842008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Bird mixed-flocks and nuclear species in a tecoma savanna in the Pantanal

Abstract: In bird mixed flocks, a prominent species, the so-called nuclear species, improves the cohesion and maintenance of the flocks, while other less conspicuous species are assumed as satellite. In this study we described the composition, as well as examined the existence of both nuclear and satellite species in mixed flocks of a savanna in the Pantanal. The observations were developed using three transects during the dry season of 2002. Bird species abundance and respective rate of participation in mixed flocks we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In agreement with our results, Hutto (1994) and Gram (1998) suggested that the congeneric P. caerulea, a migratory species, plays an active nuclear role in flocks of a semi-deciduous dry forest in Mexico. Similar active behavior has been observed for other nuclear species such as the flycatcher Suiriri suiriri in our https://journal.afonet.org/vol94/iss3/art3/ study area (de Vasconcelos et al 2008), and in the southern Pantanal (Amaral and Ragusa-Netto 2008) during the dry season. However, we suggest that C. rufus, a flycatcher species, acts as a sentinel in flocks, however we have still not observed any situations involving alarm calls.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In agreement with our results, Hutto (1994) and Gram (1998) suggested that the congeneric P. caerulea, a migratory species, plays an active nuclear role in flocks of a semi-deciduous dry forest in Mexico. Similar active behavior has been observed for other nuclear species such as the flycatcher Suiriri suiriri in our https://journal.afonet.org/vol94/iss3/art3/ study area (de Vasconcelos et al 2008), and in the southern Pantanal (Amaral and Ragusa-Netto 2008) during the dry season. However, we suggest that C. rufus, a flycatcher species, acts as a sentinel in flocks, however we have still not observed any situations involving alarm calls.…”
Section: Discussionsupporting
confidence: 84%
“…Bird richness in this ecosystem represents about 30% of the Brazilian avifauna, and species inhabit different ecological niches and types of vegetation (Sick 1997, Gwynne et al 2010. Birds also participate in mixed-species flocks through a gradient of grassy-shrubby-forest vegetation (Amaral and Ragusa-Netto 2008), which can also be strongly influenced by seasonal change in the hydrological cycle (de Pinho et al 2017). Moreover, the Pantanal comprises a natural mosaic of patchy forests, savannas, and grasslands, covered by water during the flood season (January to March), but more accessible during the dry (May to September) and the beginning of the rainy (October to April) season (Junk et al 2006, Alho 2008, Alho et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…I then provided data on predator presence as well as responses to predators and other stimuli to evaluate potential antipredator benefits of association with C. diana. I predicted that C. diana would most often be the first caller to harmful stimuli, as found in previous studies of C. diana and other nuclear species (Bshary and Noë 1997a;Amaral and Ragusa-Netto 2008).…”
Section: Introductionmentioning
confidence: 63%
“…Bird species that promote the formation and maintenance of mixed flocks are often termed ''nuclear species,'' and associating species are termed ''satellite species'' (Moynihan 1962). Nuclear species have conspicuous calls, movement, and coloration, and effective antipredator detection (Amaral and Ragusa-Netto 2008). The nuclear species concept is also relevant for primatology, and at Taï Forest, Côte d'Ivoire the vividly colored and very vocal Diana monkey (Cercopithecus diana) has been called a nuclear species for red colobus monkeys (Procolobus badius), Campbell's monkey (C. campbelli), and lesser spot-nosed monkeys (C. petaurista) by Bshary and Noë (1997a).…”
Section: Introductionmentioning
confidence: 99%
“…This is interesting as so far the Long-tailed finch was more seen as a superior competitor with respect to nest holes [31]. In contrast, around waterholes Long-tailed finches may act as a nuclear species [46] for Gouldian finches. Why they prefer this species above others is unknown but may be explained with their co-occurrence across the species’ range and their similar ecological requirements, although the Long-tailed finch is much more a generalist than the Gouldian finch [31].…”
Section: Discussionmentioning
confidence: 99%